2002
DOI: 10.1038/sj.cr.7290104
|View full text |Cite
|
Sign up to set email alerts
|

Telomere and telomerase in oncology

Abstract: Shortening of the telomeric DNA at the chromosome ends is presumed to limit the lifespan of human cells and elicit a signal for the onset of cellular senescence. To continually proliferate across the senescent checkpoint, cells must restore and preserve telomere length. This can be achieved by telomerase, which has the reverse transcriptase activity. Telomerase activity is negative in human normal somatic cells but can be detected in most tumor cells. The enzyme is proposed to be an essential factor in cell im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
5

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 42 publications
0
34
0
5
Order By: Relevance
“…However, telomerase activity is normally found in lymphocytes; and considering that leukoplakias are often associated with chronic inflammation in the submucosa, interpretations of telomerase activity may be confounded. 40,41 Jiang et al 33 analyzed oral leukoplakias with respect to loss of heterozygosity (LOH) and found a high prevalence of LOH in oral leukoplakias and an increase in LOH from leukoplakias to foci of early cancerization. These results notwithstanding, their prognostic impact was not documented.…”
Section: Molecular Markers Of Malignant Transition In Oral Premalignamentioning
confidence: 99%
“…However, telomerase activity is normally found in lymphocytes; and considering that leukoplakias are often associated with chronic inflammation in the submucosa, interpretations of telomerase activity may be confounded. 40,41 Jiang et al 33 analyzed oral leukoplakias with respect to loss of heterozygosity (LOH) and found a high prevalence of LOH in oral leukoplakias and an increase in LOH from leukoplakias to foci of early cancerization. These results notwithstanding, their prognostic impact was not documented.…”
Section: Molecular Markers Of Malignant Transition In Oral Premalignamentioning
confidence: 99%
“…Estas estruturas, compreendem sequências de nucleótidos que protegem as extremidades dos cromossomas da sua degeneração e da fusão com outros cromossomas, prevenindo a instabilidade genómica (22,34,105,123,150,170). Para além destas funções, os telómeros desempenham também um papel importante indirecto no controlo da proliferação das células normais e no crescimento anormal do cancro (81,105,150).…”
Section: Teoria Dos Telómerosunclassified
“…Para além destas funções, os telómeros desempenham também um papel importante indirecto no controlo da proliferação das células normais e no crescimento anormal do cancro (81,105,150). Na ausência da telomerase, uma enzima que adiciona repetições sucessivas de bases de DNA telomérico aos telómeros, em cada duplicação celular a célula perde entre 50 e 201 pares de bases (bp) de DNA telomérico (105,170). Aparentemente, as células humanas deixam de se dividir quando o comprimento final do DNA telomé-rico atinge aproximadamente 4-7 bp (15 a 20 nas células germinais) prevenindo, assim, a fusão com outros cromossomas (105).…”
Section: Teoria Dos Telómerosunclassified
“…They fail to acquire telomerase activity in successive cultures and become senescent. In contrast, telomerase activity has been detected in numerous cancer cells and tissues (Kim et al, 1994;Mu and Wei, 2002).…”
mentioning
confidence: 99%
“…They fail to acquire telomerase activity in successive cultures and become senescent. In contrast, telomerase activity has been detected in numerous cancer cells and tissues (Kim et al, 1994;Mu and Wei, 2002).Brain tumors in which telomerase activity has been detected include glioblastoma, anaplastic astrocytoma, oligodendroglioma, and meningioma (Hiraga et al, 1998;Langford et al, 1995;Sano et al, 1998). Increased expression of the telomerase RNA component was found to be associated with increased cell proliferation in astrocytomas and ependymomas (Grosso and Schiffer, 1998).…”
mentioning
confidence: 99%